Electroacupuncture for mild-to-moderate dry eye: study protocol for a multicentre, randomised, single-blind, sham-controlled trial - Yue Zhao; Guang Yang; Yun-Qiong Lu; Mei-Yan Li; Jue Hong; Yan-Ting Yang; Xue-Jun Wang; Xie-He Kong; Zhao Ma; Xin-Yun Huang; Yue-Lan Zou; Xing-Tao Zhou; et al. (BMJ Open)
Introduction Dry eye (DE) is a multifactorial ocular surface disease causing considerable medical, social and financial implications. Currently, there is no recognised long-term, effective treatment to alleviate DE. Clinical evidence shows that electroacupuncture (EA) can improve DE symptoms, tear secretion and tear film stability, but it remains controversial whether it is just a placebo effect. We aim to provide solid clinical evidence for the EA treatment of DE.Methods and analysis This is a multicentre, randomised, sham-controlled trial. A total of 168 patients with DE will be enrolled and randomly assigned to EA or sham EA groups to receive 4-week consecutive treatments and follow-up for 24 weeks. The primary outcome is the change in the non-invasive tear break-up time (NIBUT) from baseline to week 4. The secondary outcomes include tear meniscus height, the Schirmer I test, corneal and conjunctival sensation, the ocular surface disease index, corneal fluorescein staining, the numerical rating scale and the Chinese DE-related quality of life scale.Ethics and dissemination The trial protocol and informed consent were approved by the Ethics Committee of Yueyang Hospital of Integrated Traditional Chinese and Western Medicine Affiliated to Shanghai University of Traditional Chinese Medicine (identifier: 2021–119), Shanghai Eye Disease Prevention and Treatment Center (identifier: 2022SQ003) and Eye and ENT Hospital of Fudan University (identifier: 2022014).Trial registration number NCT05552820.